Overcoming COVID-19 in Bhutan lessons from coping with the pandemic in a tourism-dependent economy - Asian Development Bank (Manila,Philippines Asian Development Bank, 2021)
Assesses the Government of Bhutan's financial relief measures for the most affected people, as well as programs and other interventions to address the impact of the coronavirus disease (COVID-19) pandemic.
Background - - Objective and Structure - - Socioeconomic Impacts - - Immediate Interventions: Proactive and Decisive Public Health Responses - - Socioeconomic Interventions: The Comprehensive National Response to COVID-19 - - Special Focus: Strengthening Tourism for Recovery and Resilience - - Economic Contingency Plan: Tourism Resilience - - Tourism Reforms - - Domestic Tourism Offers Some Respite - - Bubble Tourism - - Conclusion.
Keywords: Bhutan -- Economic conditions